Gender Stereotypes and Peer Selection in STEM Domains Among Children and Adolescents. - McGuire, Luke; Hoffman, Adam J.; Mulvey, Kelly Lynn; Hartstone-Rose, Adam; Winterbottom, Mark; Joy, Angelina; Law, Fidelia; Balkwill, Frances; Burns, Karen P.; Butler, Laurence; Drews, Marc; Fields, Grace; et al. (Sex Roles, 2022)
Gender stereotypes are harmful for girls' enrollment and performance in science and mathematics. So far, less is known about children's and adolescents' stereotypes regarding technology and engineering. In the current study, participants' (N = 1,206, girls n = 623; 5–17-years-old, M = 8.63, SD = 2.81) gender stereotypes for each of the STEM (science, technology, engineering, and mathematics) domains were assessed along with the relation between these stereotypes and a peer selection task in a STEM context. Participants reported beliefs that boys are usually more skilled than are girls in the domains of engineering and technology; however, participants did not report gender differences in ability/performance in science and mathematics. Responses to the stereotype measures in favor of one's in-group were greater for younger participants than older participants for both boys and girls. Perceptions that boys are usually better than girls at science were related to a greater likelihood of selecting a boy for help with a science question. These findings document the importance of domain specificity, even within STEM, in attempts to measure and challenge gender stereotypes in childhood and adolescence.